Study on ABCG2 Gene Polymorphism in Jaffarabadi and Surti Buffaloes by PCR-RFLP - Patel, Santul; Brahmkshtri, Balkrishna; Ramani, Umed; Pandya, Guarav; Dangar, Nikhil; Devkatte, Savita; Kharadi, Vishnu (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
In the present study, considering the role of ABCG2 gene in milk production and composition traits, Jaffarabadi and Surti buffaloes werescreened for its polymorphism. PCR- RFLP technique was used to detect the polymorphism in 292 bp (partial intron 13 and exon 14) and240 bp (partial exon 14) fragments of ABCG2 gene using HhaI and PstI restriction enzymes, respectively. The absence of polymorphismin ABCG2 gene in the study for partial intron 13 and exon 14 fragment of 292 bp as well as partial exon 14 fragment of 240 bp indicatedfixation of alleles at both the loci in Jaffarabadi and Surti buffalo breeds.
Keywords: ABCG2 gene; Jaffarabadi; Surti buffaloes; Milk production and composition trait; PCR-RFLP; Polymorphism